2022
DOI: 10.3389/feduc.2022.979291
|View full text |Cite
|
Sign up to set email alerts
|

The use of virtual and augmented reality in science and math education in Arab countries: A survey of previous research studies

Abstract: The aim of this study was to present a survey of research relating to the use of virtual and augmented reality in science and math education in Arab countries after 2012. The research studies were collected from several sources that include a set of common Arabic research database, a set of English research database, and popular search engines. Thirty three research studies were found related to the use of virtual and augmented reality in science and math education in Arab countries. These studies were examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Rahmat et al (2023) found that while teachers are still relatively unfamiliar with AR technology, they expressed positive perspectives on its potential in science education (Rahmat et al, 2023). Similarly, Abutayeh et al (2022) emphasized the need for more research focusing on teachers' views and expectations regarding the use of AR in science and math education (Abutayeh et al, 2022). They found that using AR simulations on computers and smartphones has led to significant improvements in students' learning outcomes compared to traditional teaching methods.…”
Section: Introductionmentioning
confidence: 99%
“…Rahmat et al (2023) found that while teachers are still relatively unfamiliar with AR technology, they expressed positive perspectives on its potential in science education (Rahmat et al, 2023). Similarly, Abutayeh et al (2022) emphasized the need for more research focusing on teachers' views and expectations regarding the use of AR in science and math education (Abutayeh et al, 2022). They found that using AR simulations on computers and smartphones has led to significant improvements in students' learning outcomes compared to traditional teaching methods.…”
Section: Introductionmentioning
confidence: 99%